Field dodder – How to control it? - Sarić-Krsmanović, Marija M; Vrbnicanin, Sava P (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Broad geographic distribution and spectrum of hosts make field dodder, Cuscuta campestris, one of the most widespread and most harmful pests among flowering parasitic plants. Field dodder may become a problem in vegetable nurseries (e.g. tomato, sweet pepper and cabbage) or in potato or some other crop grown in plastic  greenhouses. However, the most devastating damage comes from field dodder outbreaks in newly-established perennial legume crops (alfalfa, clover, etc.), which are generally the preferred hosts of this parasitic flowering species. Apart from alfalfa and clover, an expansion of field dodder has been observed in recent years in sugar beet, too.Different measures are available for controlling field dodder, from preventive (pureseeding material, tolerant cultivars, etc.), to mechanical removal (mowing and hand weeding) to herbicide treatments. The most successful control of field dodder requires a systematic approach ensured through integrated protection, which contributes to a more effective control of parasitic flowering plants.
Keywords: Field dodder; Herbicides; Control